2022
DOI: 10.1111/phpp.12827
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell‐derived exosome miR‐29b‐3p alleviates UV irradiation‐induced photoaging in skin fibroblast

Abstract: Background Mesenchymal stem cells‐derived exosome (MSCs‐exo) was identified to reduce photoaging. The purpose of this study was to investigate the potential role of microRNA (miR)‐29b‐3p derived from bone marrow MSCs‐exo (BMSCs‐exo) in photoaging. Methods Exosomes were isolated from BMSCs and verified by Western blot. A photoaging cell model was constructed by UVB irradiation of human dermal fibroblasts (HDFs). Quantitative real‐time PCR (RT‐qPCR) was performed to detect the mRNA levels of miR‐29b‐3p, collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Results from the present findings presented that BMSCs-exo can promote the secretion of collagen I of HDFs, thus alleviating the inhibition of HDFs. Consistently, our preliminary findings have confirmed that BMSCs-exo exerts a protective role in improving skin photoaging function, and miR-29b-3p is involved in the regulatory mechanism [22]. Extracellular matrix metalloproteinases (MMPs) are key enzymes in the process of collagen degradation.…”
Section: Discussionsupporting
confidence: 78%
“…Results from the present findings presented that BMSCs-exo can promote the secretion of collagen I of HDFs, thus alleviating the inhibition of HDFs. Consistently, our preliminary findings have confirmed that BMSCs-exo exerts a protective role in improving skin photoaging function, and miR-29b-3p is involved in the regulatory mechanism [22]. Extracellular matrix metalloproteinases (MMPs) are key enzymes in the process of collagen degradation.…”
Section: Discussionsupporting
confidence: 78%
“…Antioxidant effect through the expression of glutathione S-transferase α 4 In vitro [ 352 ] Lactobacillus plantarum Skin aging Decrease MMP-1 mRNA expression and elastase activity and increase filaggrin mRNA expression and HAS2 protein expression. In vitro, in vivo [ 353 ] Apple Skin aging and reparation Negative effect on the activity of Toll-like Receptor 4 and NF-κB pro-inflammatory pathway In vitro [ 354 ] Human amniotic fluid-derived stem cells Skin wound healing Decreased secretion of inflammation-associated cytokines through CXCR4 In vivo [ 355 ] Human UCMSCs Molecular mechanism in skin wound healing PI3K/AKT pathway is regulated by phosphatase and tensin homolog In vitro [ 356 ] BMSCs Photoaging by UVB irradiation Suppressed the mRNA of MMP-2 In vitro [ 357 ] Hypoxia-pretreated ASCs Regenerative effects in UVB-induced skin injury circ-Ash 1l targets miR-700-5p and GPX4, and miR-700-5p target GPX4. In vitro, in vivo [ 358 ] Epidermal stem cells Skin wound healing May inhibit the differentiation of fibroblasts to myofibroblasts via suppressing TGF-β1 expression via miR-425-5p and miR-142-3p In vivo [ 359 ] Human dermal fibroblast Photoaging by UVB irradiation Increased procollagen type I expression and a decrease in MMP-1 expression, mainly through the downregulation of TNF-α and the upregulation of TGF-β …”
Section: Exosomes In Regenerative Medicine: Tissue-specific Applicationsmentioning
confidence: 99%
“…The pathology of wound healing is regulated by a wellorchestrated processed including inflammation, reepithelialization, reformation, angiogenesis, and collagen remodeling (Singer and Clark, 1999). MSC-exosomes are believed to have equivalent biological effects to MSCs in tissue regeneration, homeostasis, and wound healing (Yeo et al, 2013;Ramasubramanian et al, 2019;He et al, 2022;Luo et al, 2022;Yan et al, 2022). They can exert their effects on receptor cells by modifying gene expression and protein production.…”
Section: Therapeutic Potential Of Msc-exosomes In Skin Tissue Regener...mentioning
confidence: 99%